2017
DOI: 10.1016/j.nut.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with concentrated milk protein in patients undergoing hematopoietic stem cell transplantation

Abstract: WPC intake ≥40% of DPR helped to reduce the severity and duration of OM. The use of WPC in patients undergoing HSCT was shown to be safe, encouraging new studies in this population to assess its action mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The neutropenia duration was approximately 9 days, similar to the previously work performed by our group (2017) [18], in which a nutritional supplementation was applied to patients undergoing HSCT and shows overall mean duration of neutropenia of 9.87 days varying 6.80 days.…”
Section: Discussionsupporting
confidence: 86%
“…The neutropenia duration was approximately 9 days, similar to the previously work performed by our group (2017) [18], in which a nutritional supplementation was applied to patients undergoing HSCT and shows overall mean duration of neutropenia of 9.87 days varying 6.80 days.…”
Section: Discussionsupporting
confidence: 86%
“…Some interventions, such as that of clarithromycin (221), celecoxib (92, 114), Chinese herbal medicine (89), whey protein concentrate (147), dexamethasone mouth wash (157) and TGF-β2 (43), have been subject to trials in humans, but have not yet resulted in general recommendations. Some authors suggested beneficial effects of IL-11 therapy (48) but others reported a high rate of toxicity and mortality in a small group of patients given the same dose of rhIL-11 (11).…”
Section: Models Of Cim In Rodents Strengths and Limitationsmentioning
confidence: 99%
“…No effect was found on mucositis. However, subgroup analysis suggested beneficial effects on duration and severity of oral mucositis in patients receiving the highest amounts of the protein supplement . A possible protective effect on the gastrointestinal mucosa of milk bioactives is supported by animal studies in rodents, in which administration of factors from bovine milk or whey has shown beneficial effects against chemotherapy‐induced gut damage .…”
Section: Discussionmentioning
confidence: 99%
“…However, subgroup analysis suggested beneficial effects on duration and severity of oral mucositis in patients receiving the highest amounts of the protein supplement. 34 A possible protective effect on the gastrointestinal mucosa of milk bioactives is supported by animal studies in rodents, in which administration of factors from bovine milk or whey has shown beneficial effects against chemotherapy-induced gut damage. 35,36 Most of the proposed beneficial compounds in milk are present in higher concentration in colostrum, compared with mature milk, and whole bovine colostrum has been suggested as a possible intervention against chemotherapy-induced mucositis.…”
Section: Discussionmentioning
confidence: 99%